Non-contact in-process ultrasonic screening of thin fusion welded joints. (April 2021) - Vasilev, Momchil; MacLeod, Charles; Galbraith, Walter; Javadi, Yashar; Foster, Euan; Dobie, Gordon; Pierce, Gareth; Gachagan, Anthony
Abstract: Joining of metal structures, or welding, plays a critical role in our modern world, where safety critical welds of thin sheet metals are used in pipework, nuclear cannisters and aircraft ducting among others. A potential failure in such welds could prove to be catastrophic, hence the need for thorough inspection and testing. With the ever-increasing automation of welding operations, manually deployed Non-destructive Evaluation (NDE) has become a major bottleneck in the supply chain. This paper introduces for the first time, non-contact gas-coupled ultrasonic sensors deployed in-process during weld deposition, for screening of weld penetration directly at the point of manufacture. 3 mm thick mild steel plates were butt-welded together using Gas Tungsten Arc Welding (GTAW) while non-contact air-coupled ultrasonic transducers, generating surface guided Lamb waves, performed inspection screening of the weld seam. Optimised Signal-to-Noise Ratio (SNR) was achieved through a customised acoustic matching layer, low-noise amplifiers and real-time signal processing. By performing multiple trials at varying levels of welding input power (0.59 kJ/mm to 1.03 kJ/mm), it was demonstrated that the amplitude of the through transmission A0 Lamb wave is correlated to the Weld Penetration Depth (WPD) and can be used for on-line weld quality screening. Advantages of the outlined method include higher production rates, reduced levels of scrap and higher production quality in regards to thin metal sheet welded components.